The intestinal microbiota impacts nutritional immunity and resistance to Acinetobacter baumannii pneumonia - Erin R. Green; Nicholas M. Negretti; Tess H. Brunner; Nicolas G. Shealy; Felipe A. Moser; Sydney L. Drury; Kacie A. Traina; Valeria M. Reyes Ruiz; Tzushan S. Yang; Christopher J. Lehmann; Mariana X. Byndloss; Raf Van de Plas; et al. (Proceedings of the National Academy of Sciences, 2026)
Broad-spectrum antibiotics are frequently administered to intensive care unit patients as part of empiric care. This treatment has been associated with subsequent infections by the emerging nosocomial pathogen Acinetobacter baumannii ; however, the mechanisms underlying this linkage remain unclear. Here, we observe an association between antibiotic treatment and microbiota disruption that precedes A. baumannii infection in a hospitalized patient cohort and demonstrate in a murine model that broad-spectrum antibiotic administration drives susceptibility to intranasal infection with this pathogen. Reconstitution of the intestinal microbiota by fecal microbiota transplant restores control of A. baumannii bloodstream dissemination, implicating microbiota dysbiosis as a key driver of pulmonary disease. Using single-cell RNA sequencing, we determine that antibiotic pretreatment reduces the abundance of transcripts related to phagocyte effector functions in the lung, including nutritional immunity pathways that restrict pathogen access to essential nutrient metals. Depletion studies identify neutrophils and inflammatory monocytes as central mediators of microbiota-dependent protection, and loss of the nutritional immunity components lipocalin-2 or calprotectin abrogates the effects of antibiotics on infected mice, demonstrating a causal relationship between microbiota dysbiosis and impaired phagocyte-mediated nutritional immunity. Together, these findings provide a mechanism for the increased severity of A. baumannii pneumonia following antibiotic exposure and highlight the intestinal microbiota as a potential therapeutic target to prevent nosocomial infections with this and other healthcare-associated pathogens.